Review on the Fundamental Aspects of Petroleum Oil Emulsions and Techniques of Demulsification - Issaka, Souleyman A.; Nour, A. H.; R. M., Yunus (OMICS International, 2015)
This review is aimed to introduce a comprehensive survey on the most prominent and sustainable techniques and methods that could abate the environmental worries as well as financial insecurities in treating petroleum emulsions, since the existence of water is not desired because of the paramount troubles it may cause on the processing streamlines, as well as financial cost associated with transporting water mixed with petroleum. Currently, the most commonly used method for treating petroleum emulsion is the application of chemical additives, known as demulsifiers. Althogh, there are many other methods that are claimed to be more favorable from economic and environmental perspectives, yet, have not being fully put into real life practice, because of the drawbacks and disadvantages. In this review, several techniques have been surveyed including, chemical, electrical, membrane, centrifuge, bacteria, air floatation, ultrasonic, and microwave. Based on this Theoretical survey, silcone based demulsifiers were reported to be very effective and environmental friendly, but expensive. Also microwave and ultrasonics were reported to be very effective in treating petroleum emulsion and could be recommended as future ulternatives for treating petroleum emulsions.